Modeling Current and Future Potential Distributions of Milkweeds and the Monarch Butterfly in Idaho - Svancara, Leona K.; Abatzoglou, John T.; Waterbury, Beth (Frontiers in Ecology and Evolution, 2019)
Monarch butterflies (Danaus plexippus) are widespread in North America but have experienced large rangewide declines. Causes of recent declines likely involve multiple biotic and abiotic stressors including climate change and loss and degradation of native milkweed (Asclepias spp.), monarchs’ obligate larval host plant. Recent broad-scale modeling efforts suggest milkweed and monarch distributions in the eastern United States will expand northward during summer months while fine-scale modeling of western population overwintering sites in California indicate shifts inland and upward in elevation. However, species’ response to climate measures varies at sub-regional scales across its range and both the impacts of climate change and potential adaptation measures may be sensitive to the spatial scale of climate data used, particularly in areas of complex topography. Here, we develop fine-scale models of monarch breeding habitat and milkweed distributions in Idaho, an area at the northern extent of the monarch breeding range in North America and important in western overwintering population recruitment. Our models accurately predict current distributions for showy milkweed (A. speciosa), swamp milkweed (A. incarnata), and monarch with AUC (area under the receiver operating characteristic curve) = 0.899, 0.981, and 0.929, respectively. Topographic, geographic, edaphic, and climatic factors all play important roles in determining milkweed and, thus, monarch distributions. In particular, our results suggest that at sub-regional and fine-scales, non-climatic factors such as soil depth, distance to water, and elevation contribute significantly. We further assess changes in potential habitat across Idaho under mid-21st century climate change scenarios and potential management implications of these changing distributions. Models project slight decreases (-1318km2) in potential suitable habitat for showy milkweed and significant increases (+5830km2) for swamp milkweed. Projected amounts of suitable habitat for monarch are likely to remain roughly stable with expansion nearly equal to contraction under a moderate scenario and slightly greater when under the more severe scenario. Protected areas encompass 8% of current suitable habitat for showy milkweed, 11% for swamp milkweed, and 9% for monarch. Our study shows that suitable habitat for monarchs and/or milkweeds will likely continue to be found in managed areas traditionally seen as priority habitats in Idaho through mid-century.